AKTIVITAS ANTIMIKROBA Lactobacillus plantarum 1 YANG DIISOLASI DARI SUSU KEDELAI TERFERMENTASI SPONTAN - Arsi Wisti; Yusmarini '; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of the study was to determined whether the isolates of Lactobacillus plantarum1 isolated from spontaneous sly fermented soymilk as well as cell-free supernatants have antimicrobial properties against pathogenic bacteria. This research was carried out experimentally using completely randomized design(CRD) with four isolates as treatments and four eplications. Antimicrobial activity was tested using the well diffusion method and the paper disc diffusion. Results of analysis of variance showed that the antimicrobial activity of lactic acid bacteria isolates and cell-free supernatant of thebacteriumEscherichiacoliFNCC-19 and Staphylococcus aureusFNCC-15 were significantly different (P <0.05).Average inhibition zone diameter isolates of lactic acid bacteria against bacteria Escherichia coli FNCC-19 ranged from 0.00 to 5.95 mm and the diameter of inhibition zone Staphylococcus aureus FNCC-15 ranged from 0.00 to 4.38 mm. The average value of inhibition zone diameter of the cell-free supernatant of the bacterium Escherichia coli FNCC-19 ranged from 0.50 to 1.70 mm. The diameter of inhibition zone against Staphylococcus aureus FNCC-15 ranged between 0.40-0.50 mm. The results of this study indicate that the isolates of Lactobacillusplantarum1R.1.3.2and the supernatant thas greater antimicrobial activity than isolates of Lactobacillusplantarum1R.11.1.2. Keywords:Antimicrobials, Lacticacid bacteria and Lactobacillusplantarum 1